Univentricular Heart - Khairy, Paul; Poirier, Nancy; Mercier, Lise-Andrée (Circulation (New York, N.Y.), 2007)
As early as 1699, Chemineau described a heart composed of 2 auricles but only 1 ventricle. 1 The univentricular heart has since fascinated the medical community. Unique in its complexity and scope, the univentricular heart has sparked intense debates about embryology and nomenclature, challenged our understanding of cardiovascular physiology and hemodynamics, and inspired some of the most creative surgical and interventional approaches in human history. The present report provides an overview of the nomenclature and classification of the univentricular heart, epidemiology and pathological subtypes, genetic factors, physiology, clinical features, diagnostic assessment, therapy, and postoperative sequelae. Although the present report touches on issues applicable to neonates and children with univentricular hearts, the focus is on information of interest and relevance to the adult cardiologist.